Preliminary Investigation of AI Adoption among Healthcare Practitioners in Pakistan: AI Adoption among Healthcare Practitioners - Habib, Samrat; Khan, Zafar Ullah; Nawaz, Ali; Salman, Rao; Saeed, Umer; Saeed, Saman; Habib, Taha (Pakistan Journal of Health Sciences, 2025)
Artificial intelligence (AI) is progressively revolutionizing healthcare systems globally, delivering innovative solutions for diagnosis, treatment, and operational efficiency. However, its acceptance among healthcare providers in Pakistan remains unexplored. Objectives: To explore the trends of artificial intelligence on healthcare professionals’ knowledge, attitudes, and practices in Pakistan and to focus on variations across medical specialities, professional experiences, and work environments. Methods: A cross-sectional survey was conducted from May to July 2024, using Google Surveys to collect data from 321 healthcare professionals across various medical specialties in Pakistan. Structured questionnaires were distributed electronically, and the responses were analyzed using Chi-Square tests to determine associations between AI knowledge, attitudes, and professional characteristics. Results: Results obtained indicated varying levels of AI awareness and practice, with notable disparities across different specialties and experience levels. Younger professionals with less experience considerably accepted AI technologies, whereas relatively more experienced professionals exhibited increasing reluctance to adopt AI technology in their professions. Positive attitudes toward AI were more prevalent in academic and tertiary care settings compared to primary care environments and medical teaching. Conclusions: This study concludes that there is a crucial knowledge gap and poor AI adoption among Pakistan’s healthcare practitioners, which is compounded by insufficient training and technological constraints. Addressing these challenges is critical for attaining AI’s potential in improving healthcare outcomes.